2002
DOI: 10.1590/s0101-81752002000400026
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of gills of the seawater fish Cathorops spixii (Agassiz) (Ariidae) by scanning and transmission electron microscopy

Abstract: ABSTRACT. Gills of the seawater fi sh Cat/w raps spixii (Agassiz, 1829) were submitted to ro uti ne processing for observation in scanning and transmission electron microscopy. The wrinkled surface of the gill filaments showed well-defined cellular ultrastructures. Microridges on cellular surface were projected over all gill structures, including respiratory lamellae. Chloride cells were usually at primary lamellae. Some rod let cells were fo und. Mucous secretory cells were uncommon at all parts of the gill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
(6 reference statements)
1
9
0
1
Order By: Relevance
“…Chloride cells are primary site of osmo-regulation in euryhaline fish. However, fish inhabiting in the freshwater possess chloride cells with wider apical surface, less evident crypts and less in abundance [19]. This observation agrees to the present study that showed a low occurrence of chloride cells.…”
Section: Discussionsupporting
confidence: 93%
“…Chloride cells are primary site of osmo-regulation in euryhaline fish. However, fish inhabiting in the freshwater possess chloride cells with wider apical surface, less evident crypts and less in abundance [19]. This observation agrees to the present study that showed a low occurrence of chloride cells.…”
Section: Discussionsupporting
confidence: 93%
“…The prominent angle of curvature at the union of short epibranchials and long and extensive ceratobranchials, toward the dorsal side, closer to the neurocranium of the first to fourth pairs of gill arches, of R. rita has also been characteristically reported in other fish species with similar feeding habits. These include Plagioscion squamosissimus, an opportunistic carnivorous feeder, preferentially a fish eater (Mazon et al, 1998), Eugerres brasilianus, an omnivorous feeder, feeding mainly on small organisms (Eiras-Stofella and Charvet-Almeida, 2000), and Cathorops spixii, which feeds primarily on bivalves, shrimps, brittle stars, and worms (Eiras-Stofella and Fank-de-Carvalho, 2002). In contrast, gill arches either lack an angle of curvature in filter-feeding mullets Mugil cephalus (Hossler et al, 1979), M. curema, M. liza, andM.…”
Section: Discussionmentioning
confidence: 99%
“…EirasStofella and Charvet-Almeida (1997, 2000 and Eiras-Stofella and Fank-de-Carvalho (2002) gave a brief account of the surface morphology of gill arches and gill rakers while describing gills in several fish species having different feeding habits.…”
mentioning
confidence: 99%
“…Selection of the BaII representing the other gill-arches of the fish was performed according to previously established methodologies in other researches (Eiras-Stofella et al, 2001;Eiras-Stofella & Fank-de-Carvalho, 2002).…”
Section: Methodsmentioning
confidence: 99%